Imperial Rule and Long-Run Development: Evidence on the Role of Human Capital in Ottoman Europe. (September 2022) - Popescu, Bogdan G.; Popa, Mircea
This study examines the effects of Ottoman imperial rule on long-run development in Europe. Using a novel geographical dataset that tracks territorial changes at the sub-national level over 600 years, we identify a negative effect of Ottoman rule on modern economic performance. Contemporary survey data provides strong support for a causal mechanism involving reduced human capital accumulation. This insight is confirmed by a regression discontinuity analysis using historical data from Romania. We uncover large causal effects of Ottoman rule on literacy rates from the 19th century, which persisted throughout the 20th century. We argue that the late adoption of the printing press in the empire was an important determinant of low human capital accumulation and illustrate this using data on the spread of the printing press.